2010
DOI: 10.1002/ajpa.21400
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the study of Romanization in Britain: A regional perspective of cultural change in late Iron Age and Roman Dorset using the Siler and Gompertz–Makeham models of mortality

Abstract: This is the first study of Romanization to use the Siler and Gompertz-Makeham models of mortality in order to investigate the health consequences of the 43 AD conquest of Britain. The study examined late Iron Age and Romano-British populations (N=518) from Dorset, England, which is the only region of Britain to display continuity in inhumation burial practice and cemetery use throughout the two periods. Skeletal evidence for frailty was assessed using cribra orbitalia, porotic hyperostosis, periosteal lesions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 94 publications
1
34
0
1
Order By: Relevance
“…We hypothesize that males in this Roman 6 border community encountered greater hazards in their lives than the females. This outcome would be in agreement with other provincial Roman studies that have found males to be at greater risk for mortality, possibly due to differences in 'environmental stressors associated with employment' (Redfern and Dewitte 2011a;Redfern and DeWitte 2011b, p. 203). Aquincum males are expected to have a higher overall fracture prevalence and demonstrate injury types that are associated with strenuous activities.…”
supporting
confidence: 91%
“…We hypothesize that males in this Roman 6 border community encountered greater hazards in their lives than the females. This outcome would be in agreement with other provincial Roman studies that have found males to be at greater risk for mortality, possibly due to differences in 'environmental stressors associated with employment' (Redfern and Dewitte 2011a;Redfern and DeWitte 2011b, p. 203). Aquincum males are expected to have a higher overall fracture prevalence and demonstrate injury types that are associated with strenuous activities.…”
supporting
confidence: 91%
“…For example, comparison of patterns of mortality deceleration requires highquality data at old ages (Wrigley-Field 2014), which might not be possible in bioarchaeological research, even with the application of newer age-estimation methods that produce better estimates for the oldest individuals Milner and Boldsen 2012;Wittwer-Backofen et al 2004). There has, however, been an increase in bioarchaeological research that is explicitly designed to detect heterogeneity in frailty and selective mortality using observable skeletal stress markers and other factors (such as sex or socioeconomic status) that might reflect underlying frailty and measuring the association between these factors and mortality or survival (Boldsen 2005a(Boldsen , b, 2007DeWitte and Wood 2008;HughesMorey 2012;Kreger 2010;Redfern and DeWitte 2011a;Usher 2000;Wilson 2010).…”
Section: Examination Of Frailty and Demographymentioning
confidence: 98%
“…Migration in Roman military and urban populations has been explored extensively using mobility isotope studies by a number of authors (e.g., Eckardt 2010; Eckardt et al 2014), resulting in a substantial published dataset (see also, Martiniano et al 2016). Bioarchaeological studies have observed disease differences between pre-Roman (late Iron Age) and Roman populations, and also between urban and rural communities (Bonsall 2013;Redfern and DeWitte 2011a;Redfern et al 2015;Rohnbogner 2015). Regional and national datasets have established that mortality risk increases for males and subadults, with increases in the frequency of infectious and metabolic diseases, dental disease and indicators of stress post-Conquest (Redfern and DeWitte 2011b;Redfern et al 2012).…”
mentioning
confidence: 99%